Improving the Quality of Life for the Elderly through Health Education for Elderly Companion Herbal Plants - Sari, Dwi Kartika; Ulfah, Bardiyati; Wulandatika, Darmayanti (OMNICODE Journal (Omnicompetence Community Developement Journal), 2021)
The living habits of the elderly at this time are lack of exercise, lack of control or sorting out healthy food and the population does not understand about the use of herbal plants for medicine. Life habits or unhealthy behavior that often causes many diseases so that many elderly have hypertension, diabetes mellitus, high cholesterol, high uric acid, and experience rheumatism. Objective: Efforts to improve the quality of life of the elderly by conducting examinations for the elderly and education about herbal plants to accompany the elderly. This activity took place in Kamawakan Village, Loksado District, Hulu Sungai Selatan Regency with the target of the elderly. The method used is seminar and question and answer. Result: there is an increase in the knowledge of the elderly in Kamawakan Village about elderly health problems, the healthy way of life of the elderly and their prevention efforts which are known from the evaluation through pretest and posttest. Conclusion: There is an increase in the knowledge of the elderly about elderly health problems and prevention efforts so that it is hoped that the elderly can live healthy and can overcome elderly health problems by utilizing herbal plants.